Tongxinluo attenuates oxygen-glucose-serum deprivation/restoration-induced endothelial barrier breakdown via peroxisome proliferator activated receptor-α/angiopoietin-like 4 pathway in high glucose-incubated human cardiac microvascular endothelial cells. Issue 34 (21st August 2020) - Qi, Kang; Yang, Yuejin; Geng, Yongjian; Cui, Hehe; Li, Xiangdong; Jin, Chen; Chen, Guihao; Tian, Xiaqiu; Meng, Xianmin
Abstract: Background: Traditional Chinese medicine Tongxinluo (TXL) has been widely used to treat coronary artery disease in China, since it could reduce myocardial infarct size and ischemia/reperfusion injury in both non-diabetic and diabetic conditions. It has been shown that TXL could regulate peroxisome proliferator activated receptor-α (PPAR-α), a positive modulator of angiopoietin-like 4 (Angptl4), in diabetic rats. Endothelial junction substructure components, such as VE-cadherin, are involved in the protection of reperfusion injury. Thus, we hypothesized cell-intrinsic and endothelial-specific Angptl4 mediated the protection of TXL on endothelial barrier under high glucose condition against ischemia/reperfusion-injury via PPAR-α pathway. Methods: Incubated with high glucose medium, the human cardiac microvascular endothelial cells (HCMECs) were then exposed to oxygen-glucose-serum deprivation (2 hours) and restoration (2 hours) stimulation, with or without TXL, insulin, or rhAngptl4 pretreatment. Results: TXL, insulin, and rhAngptl4 had similar protective effects on the endothelial barrier. TXL treatment reversed the endothelial barrier breakdown in HCMECs significantly as identified by decreasing endothelial permeability, upregulating the expression of JAM-A, VE-cadherin, and integrin-α5 and increasing the membrane location of VE-cadherin and integrin-α5, and these effects of TXL were as effective as insulin and rhAngptl4. However, Angptl4 knock-down with small interfering RNA (siRNA) interference and PPAR-α inhibitor MK886 partially abrogated these beneficial effects of TXL. Western blotting also revealed that similar with insulin, TXL upregulated the expression of Angptl4 in HCMECs, which could be inhibited by Angptl4 siRNA or MK886 exposure. TXL treatment increased PPAR-α activity, which could be diminished by MK886 but not by Angptl4 siRNA. Conclusion: These data suggest cell-intrinsic and endothelial-specific Angptl4 mediates the protection of TXL against endothelial barrier breakdown during oxygen-glucose-serum deprivation and restoration under high glucose condition partly via the PPAR-α/Angptl4 pathway.